Snowball Cookies: social media portfolio / Mohd Ishraffil Ezzrail Mohd Jusni and Ezzat Imani Bin Muhamad Jamri - Mohd Jusni, Mohd Ishraffil Ezzrail; Muhamad Jamri, Ezzat Imani (2021)
Snowball Cookies by AE was established in 2021 by two young entrepreneurs known as Mohd Ishraffil Ezzrail Bin Mohd Jusni as founder of AE Enterprise and Ezzat Imani bin Muhamad Jamri as Chief Executive Officer of AE Enterprise. Our product called Snowball Cookies was first launched on 11th November 2021 via our Facebook Page Official known as Snowball Cookies by AE. First posting is a teaser of our product on 1st November 2021. We registered our business through Go-Ecommerce and MYEnt early October. As our one and only product, we focused on Snowball Cookies in terms of marketing, financing and future planning. Our target customer is wide because our product can be consumed and purchase at any age and gender, low and high level of income and also employed and unemployed. The purpose of this report is to acknowledge our business and what we are sell to the market using social media which is Facebook. This report consists of business description, types of posting, frequency of posting and also business insights report that we get from our Facebook Page. Snowball Cookies is a homemade melted non-baked cookies that looks exactly like snowball and we used high quality ingredients from famous brand in Malaysia and one more thing, we used special technique to cook the flour. The tastiness is premium but the price is really affordable as we want our customers feel satisfy with our product and keep repeat to purchase our product.